Teacher-children interaction and concept development in kindergarten - Rosemberg, Celia Renata (2009)
This article analyzes the interaction between teachers and children in kindergarten classrooms in order to identify and describe the discursive strategies of teachers that retrieve children's previous expressions to clarify and specify concepts represented in them. Data analyzed include 90 situations of teacher–children exchanges in 7 kindergarten classrooms located in marginal urban neighborhoods in the outskirts of the city of Buenos Aires, Argentina. The analysis followed a qualitative procedure: the constant comparative method (CitationGlaser & Strauss, 1967; CitationStrauss & Corbin, 1991). This allowed the authors to identify and describe the various ways in which teachers reconceptualize information offered by the children in ways that allow them to gradually specify, define, and characterize concepts underlying the words they use, albeit with a limited meaning. It also leads children to develop a finer differentiation and integration between concepts. Such development promotes processes of generalization and construction of hierarchical taxonomies.